Ekspresywność "ponglisza" - języka kontaktowego używanego nie tylko przez Polaków zamieszkujących kraje anglojęzyczne = Expressive means in Ponglish - a contact language variety used not only by Poles living in English-speaking countries - Majdańska-Wachowicz, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is to examine selected expressive means in Ponglish. Ponglish (a blend of "Polish" and "English"), as the name indicates, is an example of a hybrid language which mixes elements of English and Polish. As can be seen from the analysis of the data obtained from an online dictionary Ponglish.org, expressivity is arguably a major component of this language variety.
Keywords: ponglish; środki ekspresywne; słowotwórstwo; angielsko-polskie kontakty językowe; expressive means; word formation; English-Polish language contact